PERANCANGAN WEBSITE SEBAGAI MEDIA PEMASARAN ONLINE PADA INDUSTRI RUMAH TANGGA TRUST MENGGUNAKAN PRESTASHOP - Agus Fitri Yanto; Afifah Choirina Rusda (Politeknik Sawunggalih Aji, 2022)
There are a lot of food processing business activities in Purworejo, but there are still a few of them that have not been supported by modern marketing media, so the creation of a website is expected to help the business they live in in the process of marketing, ordering and selling products. Data collection techniques used in this study include observation, documentation and literature study. This research method through primary and secondary data and programming. This website is packed with various information about TRUST such as home, profile, TRUST history, TRUST destination, location, contacts, questions, checkout method, testimonials and D3 - AB Polsa. Promotion using the website has many advantages including the delivery of information about products, product prices, product quality will be conveyed to consumers clearly and also expand market share in the future. For the sake of website progress, TRUST should need to develop the display and menu design to make it more attractive, for example, discount voucher menus for price cuts so that it can attract more customer interest and develop a bank transfer payment menu with various types of bank accounts so customers can adjust to a bank account owned.